The role of career development in enhancing employee loyalty: A literature review - Olga, Lidia; Nurraihan, Faiq (Junal Ilmu Manajemen, 2025)
Employee loyalty is essential for organizational survival, and career development is recognized as a significant contributor to enhanced loyalty. This study seeks to examine the current literature about the correlation between career development and employee loyalty and to propose measures that organisations might adopt to bolster loyalty via career development. Analysis of multiple studies revealed that effective career development programs enhance job satisfaction, motivation, and employee engagement, thereby fostering organizational loyalty. Moreover, supervisory support, a conducive working environment, and work-life balance significantly contribute to cultivating robust connections between employees and the organization. Despite several studies indicating a favorable correlation between professional development and loyalty, a gap persists in the literature, particularly in the examination of the specific effects of different types of career development programs. This study advocates for organizations to establish structured career development programs, define clear career trajectories, and foster a supportive working environment. Future studies should investigate additional elements affecting this association and provide fresh insights into human resource management. This study significantly contributes to our understanding of how career development might bolster employee loyalty and facilitate organizational sustainability.